Cross-Sectional Students Conception about Eclipse and Moon Phase - Darmini, Yulyana; Hatibe,, Amiruddin; Saehana, Sahrul (Jurnal Riset Pendidikan MIPA, 2018)
This study aimed to describe the conception of junior high school students, high school and students about eclipses and the phases of the moon. Respondents involved in this study were 35 junior high school students, 24 high school students and 38 college students. The instrument used to mendeksripsikan conception as much as 10 numbers. At the first level students are expected to choose the right option right or wrong or memilh existing options. At the second level students are asked to give a reason or their reasoning on the answers chosen. Presentation answers and reasons given by the students and the students analyzed and interviewed nine respondents by category of high, medium and low. The results showed the error of misconceptions on the respondents and conception does not depend on the level of education as evidenced by the acquisition of junior high students score higher than high school students and college students. Finally, further advice is based on an error of misconceptions and research development are presented for future research. The results obtained are the respondents students and students assume the time required to rotate months is not the same as the time required months evolved, respondents can not explain well the position and phase of the moon that occurred, respondents have a better conception on the questions about the eclipse compared with Matter for the phase of the month and the level of education of the respondents did not affect the respondents have a higher conception.